Forward and inverse analysis of electromagnetic fields for MRI using computational techniques - Cobos Sanchez, Clemente (2008)
MRI has become an invaluable tool for diagnostic medicine. Its operation is based on the principles of electromagnetism that are dictated by Maxwell's equations. MRI relies on the existence of well defined, spatially and temporally controlled magnetic fields, which are usually generated by coils of wire. Human exposure to these fields has become a safety concern, especially with the increase in the strength of the magnetic fields used.